Activating Oxygen Redox in Layered NaxMnO2 to Suppress Intrinsic Deficient Behavior and Enable Phase‐Transition‐Free Sodium Ion Cathode. (25th June 2022) - Wang, Feng; Peng, Bo; Zeng, Suyuan; Zhao, Liping; Zhang, Xiaolei; Wan, Guanglin; Zhang, Hongli; Zhang, Genqiang
Abstract: P2‐type layered Nax MnO2 cathode shows great potential in practical sodium ion batteries, especially for grid‐level applications due to its eco‐friendly and cost‐effective sodium and manganese resources, and high theoretical specific capacity. However, several obstacles including severe phase transitions of P2‐O2 and P2‐P2′, low redox potential of Mn 3+ /Mn 4+, disproportionation reaction and Jahn‐Teller distortion of Mn 3+, and deficient behavior have already hindered its practical applications. Herein, a Li, Cu co‐doping strategy to tackle the mentioned obstacles by activating the oxygen redox is presented. The Li, Cu co‐doped material exhibits solid solution reaction without any phase transitions as proved by in situ X‐ray diffraction measurement and reduces the dissolution of active manganese element. With this modification treatment, it can dramatically raise the cycling stability from 30.4% to 80.1% after 150 cycles and simultaneously improves the deficient behavior due to the capacity contribution of oxygen redox at high voltage. More importantly, the coin‐cell type sodium ion full cell assembled with this cathode and commercial hard carbon anode delivers a promising energy density of 225.1 Wh kg –1 . Abstract : A Li, Cu co‐doped layered P2‐Nax MnO2 is subtly designed via a cost‐effective sol‐gel method. The co‐doped material shows phase‐transition‐free nature at high voltage due to the activation of oxygen redox, and mitigates the Jahn–Teller distortion and dissolution of Mn 2+, contributing to the enhanced rate and cyclic capability.